Synthesis and in-vitro antibacterial activity of some bis-5-(thiophen-2-yl)-carbothioamide-pyrazoline derivatives - Rani, Mamta; Yusuf, Mohamad (European Journal of Chemistry, 2012)
Five new compounds, bis-pyrazoline derivatives (2a-e) with antibacterial properties, built around the alkyl chains of varying lengths were prepared via reaction of various 1-ω-alkoxy-bis-chalcones with N-substituted thiosemicarbazide in ethanolic NaOH solution. The antibacterial activity of these compounds were evaluated by the disk diffusion method against two Gram-positive and two Gram-negative bacteria and the minimum inhibitory concentration were determined. The structures of these compounds were elucidated by IR, 1H-NMR, 13C-NMR, ESI mass spectrometry and their purities were also confirmed by elemental analyses. The formation and stereochemical features of the compounds, 2a-e, are found to be independent of the internal spacer length. The results showed that compounds 2a and 2e are better antibacterial agent compared to Gentamicin and Tetracycline.